Preparation and Magnetic Properties of Sm-Cu ion Substituted Strontium Ferrite - WU Ze; ZHANG Ruo-nan; JIN Li-guo (Journal of Harbin University of Science and Technology)
Sm-Cu substituted strontium ferrites Sr1-xSmxFe12-xCux19(x=0.00-0.20) were prepared by the solid-state reaction X-ray diffraction (XRD), scanning electron microscopy (SEM) and vibrating sample magnetometer (VSM) were employed to analyze the phase structure, morphology and magnetic performance, respectively The results show that the saturation magnetization (Ms), coercivity (Hc) and remanence magnetism (Mr) first increases and then decreases with increasing xWhen the doping amount x of Sm-Cu is 0.05, the Mr reaches a maximum value of 24.173emu/g. The doping amount x of Sm-Cu is 0.10, the Ms and Hc values turn to be the maximum values of 51.757emu/g and 809.904Oe, respectively.